Proceedings of the 2011 Winter Simulation Conference (WSC) 2011
DOI: 10.1109/wsc.2011.6147752
|View full text |Cite
|
Sign up to set email alerts
|

Including airport duty-free shopping in arriving passenger simulation and the opportunities this presents

Abstract: Simulating passenger flows within airports is very important as it can provide an indication of queue lengths, bottlenecks, system capacity and overall level of service. To date, visual simulation tools such as agentbased models have focused on processing formalities such as check-in, and not incorporate discretionary activities such as duty-free shopping. As airport retail contributes greatly to airport revenue generation, but also has potentially detrimental effects on facilitation efficiency benchmarks, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The resultant framework is demonstrated on an airport passenger facilitation case study, showing how a ABM [22], BPMN [47] and HQBN [48] can be integrated to provide whole-of-system decision support. It is found that decomposition and classification of model components as per the STS element hierarchy and three layered framework provides a systematic way to establish information flow both internally and between models via links/interface points.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The resultant framework is demonstrated on an airport passenger facilitation case study, showing how a ABM [22], BPMN [47] and HQBN [48] can be integrated to provide whole-of-system decision support. It is found that decomposition and classification of model components as per the STS element hierarchy and three layered framework provides a systematic way to establish information flow both internally and between models via links/interface points.…”
Section: Resultsmentioning
confidence: 99%
“…This is enabled via static, dynamic and behavioural object instantiations of STS elements (where an instance of a STS element is a component in the model). This section demonstrates the utility of proposed framework with a case study application in the Airports of the Future project, an Australian Research Council linkage project comprising 29 government, industry and academic organisations [22,44,41,18]. The objective of the project is to improve the efficiency, security and experience of the passenger facilitation process in airports.…”
Section: Discussion and Airport Sts Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this software is flexible for simulating various systems such as supply chain, manufacturing, processing, logistics, distribution and warehousing [7], [8]. It was also applied in many field research areas [1], [4], [5], [9], [13].…”
Section: Introductionmentioning
confidence: 99%